Clinical and histologic study of autogenous oral mucosa in experimental lamellar ketatoplasty/ Estudo clínico e histológico da mucosa oral autógena na ceratoplastia lamelar experimental - Vinícius Rivera Cardoso Prado; Ingrid Bueno Athayde; Nilo Sérgio Troncoso Chaves; Adilson Donizeti Damasceno (Semina: Ciências Agrárias, 2004)
Eight male dogs of non-specified breed, weighing about 12,4 kg, were subjected to surgical oral mucosa detachment using among others a 5 mm diameter trepan followed by it fixation on 4,5 mm diameter corneal lesion made in an eye, using 9-0 nylon thread in interrupted simple suture pattern. The animals were divided to 4 groups constituted by 2 animals, for histologic study at 15, 30, 45, 60 days of post surgical phase. Meanwhile, clinical findings such as blepharospasm, opacity, neovascularization, ocular discharge, chemosis and characteristics of the graft (vascularization, pigmentation and adhesiveness), were qualitative and quantitatively evaluated at 0-2 days, 3-7 days, 8-15 days, 16-30 days and 31-60 days of postoperative period. Blepharospasm and chemosis were more intense at initial periods, corneal opacity and vascularization (of cornea and grafts) at intermediate periods, both with regressing tendency on the latest periods. Serous mucous exsudate was predominant in higher degrees at the initial and intermediate phases and was absent on the later phases. Clinically, the integration of the graft was verified at 15th day. Pigment deposition was seen on two animals on the later periods. The microscopic study revealed on initial and intermediate periods a thick epithelium in comparasion with the underlying cornea, with vacuolization of the inmost cells, intense fibroplasia and collagen fibers deposition on a disorganized setting and intense vascularization of the graft. Mild polymorphonuclear infiltration in graft was observed at 15th day. Plasmocyte infiltration at intermediate phase was mild to moderate. On the 60th day, were observed reasonably thick epithelium with projections to stroma, moderate presence of fibrocytes, collagen on a more organized setting, vascularization ranging from mild to absent and lymphoplasmocitary infiltration in moderate degree. The results allowed us to admit that keratoplasty technique employing buccal mucosa is feasible option for tectonic and reconstructive means in dogs. Oito cães sem raça definida, machos, com peso corpóreo médio de 12,4 kg, foram submetidos a procedimentos cirúrgicos de retirada de fragmento da mucosa oral com auxílio de trépano de 5 mm com posterior aplicação sobre lesão corneana de 4,5 mm de diâmetro, produzida em um dos olhos, aplicando-se sutura simples interrompida com fio de náilon 9-0. Os animais foram divididos em 4 grupos compostos por 2 animais, para estudo histológico aos 15, 30, 45, 60 dias de pós-operatório. Simultaneamente, realizou-se estudo clínico nos períodos de 0-2 dias, 3-7 dias, 8-15 dias, 16-30 dias e 31-60 dias de pós-operatório. Blefarospasmo e quemose foram mais intensos nos períodos iniciais e opacidade corneana e vascularização (da córnea e enxerto) nos períodos intermediários, ambos com tendência de regressão nos períodos tardios. A secreção predominante foi seromucosa, sendo mais incidente nas fases iniciais e intermediárias com ausência nos tardios. Clinicamente, a integração do enxerto foi verificada no 15º dia. O estudo microscópico revelou para os períodos iniciais e intermediários intensa fibroplasia e deposição de fibras colágenas em arranjo desorganizado e vascularização do enxerto de intensa a leve entre 15º e 30º dia. Infiltrado polimorfonuclear foi observado no 15º dia, em grau discreto. Infiltrado linfoplasmocitário foi predominantemente, em grau discreto a moderado, entre o 30º e 60º dia. No 60º dia, observou-se epitelização compacta com projeções para o estroma, presença moderada de fibrócitos, colágeno em disposição mais organizada e vascularização discreta a ausente. Diante dos resultados admite-se a técnica de ceratoplastia com o emprego da mucosa bucal como opção eficiente para fins tectônicos e reconstrutivos em cães.